Some Perspectives on Societal Impacts of Past Climatic Changes - Diaz, Henry F. (History compass, 2014)
We examine a range of paleoclimatic evidence covering approximately the last 2000 years (the Common Era) to provide plausible environmental scenarios as potential drivers and stressors associated with major societal disruption in different parts of the world. The period studied covers both historical, for which there is documentary evidence of impacts, and prehistorical events, for which impacts are inferred from the archeological record. Drought appears to be the most common high-impact stressor in the historical and prehistorical records. Clearly, the adequacy of water supplies for growing food and for an array of other uses is a thread that weaves its way across time and societies. We also briefly outline some of the key physical mechanisms leading to climatic changes of a magnitude that could have led to societal disruptions. These include solar variability and large explosive volcanic eruptions, both of which affect the amount of radiant energy available to the Earth's climate system, as well as the natural internal variability of the climate system. We emphasize that climatic changes alone are unlikely to be the sole determinant cause of a given society's response - whether abandonment of settlements or bellicose action against its own members or neighbors. Often, the natural hazard is simply a catalyst for actions whose groundwork had been set in motion for some time prior. In many cases, appropriate mitigation to reduce vulnerability and efforts to enhance a society's adaptive capacity might have been enough to prevent the most extreme consequences of the nature's extremes. In that vein, we point to current conditions in the western United States, where a complex mix of past and current actions together with a rapidly changing climate are causing a plethora of problems whose solution will demand creative collaborative actions at all levels of society.